Mucocutaneous manifestations in juvenile-onset systemic lupus erythematosus: a review of literature - Chiewchengchol, Direkrit (Pediatr Rheumatol Online J, 2015)
Patients diagnosed with juvenile-onset systemic lupus erythematosus (JSLE) often have skin and oral lesions as part of their presentation. These mucocutaneous lesions, as defined by the American College of Rheumatology (ACR) in 1997, include malar rash, discoid rash, photosensitivity and oral ulcers. It is therefore essential to recognize mucocutaneous lesions to accurately diagnose JSLE. The mucocutaneous lesions can be divided into those with classical histological features (LE specific) and those strongly associated with and forming part of the diagnostic spectrum, but without the classical histological changes of lupus (LE nonspecific). A malar rash is the most commonly associated LE specific dermatological presentation. This skin manifestation is an acute form and also correlates with disease activity. Subacute (polycyclic or papulosquamous lesions) and chronic (discoid lesions) forms, whilst showing classical histological changes supportive of lupus, are less commonly associated with systemic lupus and do not correlate with disease activity. The most commonly associated skin lesions without classical lupus changes are cutaneous vasculitis, oral ulcers and diffuse non-scarring alopecia. These signs frequently relate to disease activity. An understanding of cutaneous signs and symptoms of lupus in children is important to avoid delay in diagnosis. They will often improve as lupus is adequately controlled and their reappearance is often the first indicator of a disease flare.